Superior endurance performance with ingestion of multiple transportable carbohydrates - Currell, K.; Jeukendrup, A. E. (Medicine & Science in Sports & Exercise, 2008)
Introduction: The aim of the present study was to investigate the effect of ingesting a glucose plus fructose drink compared with a glucose-only drink (both delivering carbohydrate at a rate of 1.8 g/min and a water placebo on endurance performance.